An Inversion-Free Method for Finding Positive Definite Solution of a Rational Matrix Equation. (18th August 2014) - Soleymani, Fazlollah; Sharifi, Mahdi; Karimi Vanani, Solat; Khaksar Haghani, Farhad; Kılıçman, Adem
Abstract : A new iterative scheme has been constructed for finding minimal solution of a rational matrix equation of the form X + A * X - 1 A = I . The new method is inversion-free per computing step. The convergence of the method has been studied and tested via numerical experiments.